Methane production from acidic effluent obtained from hydrogen fermentation process of food waste using continuous stirred tank reactor - Chakkrit Sreela-or (Science Faculty of Chiang Mai University, 2019)
This study investigated the effect of hydraulic retention time (HRT) on methane production from the acidic effluent of a hydrogen fermentation process of food waste using a continuous stirred tank reactor (CSTR). The CSTR was operated at 35 ± 3°C with HRTs of 12, 10, 8 and 6 days (d). The hydrogen content, methane yield (MY) and methane production rate (MPR) were increased with a decrease in HRT from 12 to 10 d. At the HRT of 10 d, the maximum methane content of 71.3%, MY of 155 mL CH4/g-COD and MPR of 4629.1 mL CH4/L d were achieved. However, a further decrease in HRT from 10 to 8 and 6 d resulted in a decrease of methane content, MY and MPR. The main soluble metabolite products obtained at the HRT of 10 d were butyric and acetic acids. The maximum energy production rate obtained at the optimum HRT of 10 d was 185.31 kJ/L d.